Entrepreneurship Education, Family Environment, and Peer Influence on Entrepreneurial Readiness: The Mediating Role of Entrepreneurial Motivation - Halim Dwi Putra; Juwita Azizah; Rani Mu'arifah (Indonesian Journal of Business and Entrepreneurship Research, 2025)
This study examines the influence of entrepreneurship education, family environment, and peer influence on entrepreneurial readiness through entrepreneurial motivation in the context of higher education. The study was motivated by the growing importance of entrepreneurial readiness as an alternative pathway to address employment challenges and promote self-employment among graduates. A quantitative approach with a descriptive explanatory design was employed to analyze the relationships among variables. Data were collected from 100 respondents through a structured questionnaire and analyzed using path analysis to test both direct and indirect effects. The findings indicate that entrepreneurship education has a positive and significant effect on entrepreneurial motivation, which subsequently contributes significantly to entrepreneurial readiness. In contrast, family environment and peer influence do not show significant direct effects on entrepreneurial readiness through entrepreneurial motivation. These results suggest that formal entrepreneurship learning plays a more decisive role in shaping motivation and readiness for entrepreneurship than external social environments. The study highlights the need to strengthen entrepreneurship-oriented learning through practical content, motivational support, and applied business experiences that can improve students’ readiness to engage in entrepreneurial activities. The findings also imply that entrepreneurship education should not only focus on theoretical understanding but also emphasize business management, marketing capability, and decision-making skills.